Immunological Study of the Heat-Labile Enterotoxins of Escherichia coli and Vibrio cholerae - Gyles, Carlton L. (1974)
Immunodiffusion experiments were conducted to associate a precipitin line with Escherichia coli heat-labile enterotoxin (LT). Wild strains of porcine and of human enteropathogenic E. coli as well as laboratory-derived enterotoxigenic variants of E. coli K-12 were used for LT antigen preparations. These were produced mainly by ultrafiltration and ammonium sulfate precipitation of broth culture supernatants. When antisera with anti-LT activity were reacted with antigen preparations from Ent(+) and Ent(−) variants of E. coli K-12, a line “a” was given by Ent(+) but not by Ent(−) preparations. Line “a” was removed by absorption of anti-LT serum with antigen preparation from an Ent(+)E. coli K-12, but was unaffected when the antigen preparation used to absorb the serum was from an Ent(−)E. coli K-12. A line identical to “a” was given by antigen preparations from wild strains of porcine enteropathogenic E. coli reacted with homologous or heterologous anti-LT sera. One human strain of enteropathogenic E. coli was shown to possess an antigen identical to that which gave rise to line “a.” To demonstrate this line it was necessary to use high concentrations of gammaglobulin and high concentrations of the crude antigen preparations. LT preparations reacted with anticholera toxin to give a line “c,” which showed a reaction of partial identity with line “b” produced by reaction of pure choleragenoid and anticholera toxin. Lines “a” and “c” gave reactions of identity.